Upaya Meningkatkan Motivasi Belajar Siswa Menggunakan Media Word Search Pada Siswa Kelas III SDIT Al-Iman - Nur Hasanah; Fatimah Azzahroh; Ning Ira Faturrohmah (Pusat Riset dan Inovasi Nasional, 2023)
Classroom Action Research (PTK) with the title Efforts to Increase Student Learning Motivation in Thematic Learning Through Media Word Search started with the low learning motivation of class III students at SDIT Al Iman Bekasi. This study aims to find solutions to increase thematic learning motivation in general. Data collection techniques using observation, interviews, and documentation. Data analysis techniques were carried out qualitatively and quantitatively with a percentage (%) questionnaire to see the success of using word search media. This research method consists of 2 cycles and each cycle consists of 4 stages, namely planning, implementing, observing, and reflecting. After being given treatment it is known that learning in cycle 2 is better than cycle 1, both in terms of process and results. Learning with word search media is proven to be able to attract students' attention and focus. The average student motivation which was originally 69% increased to 83.87% in cycle 2.